Keefektifan Problem Based Learning untuk Meningkatkan Kemampuan Literasi Matematis Siswa - Pamungkas, Megita Dwi; Franita, Yesi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2019)
This research aims to test the effectiveness of mathematics learning with the problem based learning and the conventional learning in junior high School (SMP) to improve the skills of mathematical literacy. The research uses the Quasi experiment method, with the design of the non-equivalent control group Pretest-Posttest. This study used two groups, one group as an experimental group that received the treatment of problem-based learning and one other group as a control group that received conventional learning treatment. The subject of this study was 64 students in two classes VIII at SMP Negeri 2 Magelang. The instrument used is a description test to measure the ability of students ' mathematical literacy. A large calculation of mathematical literacy skills is improved using the normalized gain equation g. The results showed that mathematics learning using problem-based learning can improve students' mathematical literacy skills. In addition, the research also concluded that there were no significant differences in the enhancement of the mathematical literacy skills of good students using both problem based learning and conventional learning. In experimental groups and control groups there is an increase in medium.Keywords: problem based learning; mathematical literacy